FACTORING AS A TOOL FOR ENHANCING THE COMPETITIVENESS OF IN TRANSPORT ENTERPRISES - Birtus, Milos; Kliestik, Tomas (Doprava a spoje, 2012)
Enterprises need for their development and success in today's highly competitive environment in addition to sufficient financial resources for the business itself also to offer its business partners additional benefits. One way to solve the dilemma is the use of factoring, which is not yet so common.